ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN USAHA EKONOMI KELURAHAN–SIMPAN PINJAM (UEK-SP) KECAMATAN RUMBAI PESISIR PEKANBARU - Rani Desmawita; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine and analyze the financial statements to measure the financial performance in Usaha Ekonomi Kelurahan-Simpan Pinjam (UEK-SP) Rumbai Pesisir, Pekanbaru. This research was conducted at UEK-SP Lembah Sari Makmur and UEK-SP Mitra Bersama Pekanbaru. The data analysis technique used in this research is descriptive analysis by analyzing financial ratios. The results of this study indicate that the ability to generate profits and the ability to manage working capital of the Savings and Loans Unit (USP) of both Lembah Sari Makmur and Mitra Bersama are better than their Kelurahan Economic Enterprises (UEK). This is due to the limited working capital of the savings and loan business unit, thus requiring the sub-district government to increase the working capital of the savings and loan unit, for example by setting aside profits from the UEK to increase the working capital of the savings and loan unit. Thus, the savings and loan unit can increase its profitability. Keywords: Financial Statement Analysis, Financial Performances, Usaha Ekonomi Kelurahan, Simpan Pinjam